ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ ЗАХИСТУ ЕЛЕКТРОТЕХНІЧНОЇ ТА РАДІОЕЛЕКТРОННОЇ АПАРАТУРИ ВІД ВИСОКОВОЛЬТНИХ КОРОТКОЧАСНИХ СПЛЕСКІВ НАПРУГИ В МЕРЕЖІ ЕЛЕКТРОЖИВЛЕННЯ - Павловський , В.О.; Гурін , В.К.; Юрченко, О.М. (Інститут електродинаміки НАН України, Київ, 2022)
A problem of electrical and radioelectronic equipment’s high energy pulse disturbance immunity is considered in the paper, in particular against microsecond high voltage disturbances (MHVD) in the power mains. It is showed causes of MHVD with amplitude up to 4 kV and even higher. A review of various protection methods against MHVD is carried out and it is shown that the use of a two-terminal network (TTN) with a significantly nonlinear current-voltage characteristic: varistors, suppressors and gas arrestors is the most effective. The report analyzes the operation principle of these two-poles and shows that the typical inclusion of such a device directly at the equipment’s input is not effective enough for cases where the high-frequency impedance of the mains is low. An L-circuit for connecting the TTN  together with an LR link is proposed, and results of computer simulation with the aid of PSPICE showed that such a scheme reduces the MHVD amplitude on the network input of the equipment by 1.5 times comparing with the typical inclusion of such a device  even under a low impedance of the mains Adding the low-pass filter to the L-circuit allows to reduce the MHVD amplitude by 40 and more times comparing with the typical inclusion of the TTN.  References 8, figures 6.